JINGLE V: Dust properties of nearby galaxies derived from hierarchical Bayesian SED fitting - Lamperti, I; Saintonge, A; De Looze, I; Accurso, G; Clark, C; Smith, M; Wilson, C; Brinks, E; Brown, T; Bureau, M; Clements, D; Eales, S; et al. (Oxford University Press, 2019)
We study the dust properties of 192 nearby galaxies from the JINGLE survey using photometric data in the 22–850  μm range. We derive the total dust mass, temperature T , and emissivity index β of the galaxies through the fitting of their spectral energy distribution (SED) using a single modified blackbody model (SMBB). We apply a hierarchical Bayesian approach that reduces the known degeneracy between T and β. Applying the hierarchical approach, the strength of the T –β anticorrelation is reduced from a Pearson correlation coefficient R = −0.79 to R = −0.52. For the JINGLE galaxies we measure dust temperatures in the range 17−30 K and dust emissivity indices β in the range 0.6−2.2. We compare the SMBB model with the broken emissivity law modified blackbody (BMBB) and the two modified blackbody (TMBB) models. The results derived with the SMBB and TMBB are in good agreement, thus applying the SMBB, which comes with fewer free parameters, does not penalize the measurement of the cold dust properties in the JINGLE sample. We investigate the relation between T and β and other global galaxy properties in the JINGLE and Herschel Reference Survey (HRS) sample. We find that β correlates with the stellar mass surface density ( R = 0.62) and anticorrelates with the H  I mass fraction ( M H  I / M * , R = −0.65), whereas the dust temperature correlates strongly with the star formation rate normalized by the dust mass ( R = 0.73). These relations can be used to estimate T and β in galaxies with insufficient photometric data available to measure them directly through SED fitting.